(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rozaki Z, Nopembereni ED, Rahayu L, Rahmawati N, Murhidayah ML, Rejeki TM, Ariffin AS, Azizah SN, Tjale MM. 2022. Farmers’ lives and adaptation strategies toward the forest and peatland fires in Indonesia: Evidence from Central and South Kalimantan, Indonesia. Biodiversitas 23: 2379-2388. The frequency of forest and peatland fires in Kalimantan is high yearly, impacting many farmers’ agricultural activities and the environment, especially in the dry season. Farmers conduct agricultural activities in this vulnerable area. This study aimed to analyze farmers’ livelihood and adaptation strategies in Central and South Kalimantan, an area prone to forest and peatland fires. The sample comprised 200 farmers as respondents while the data were collected using a semi-structured questionnaire and analyzed using descriptive and rank spearman analysis. The results showed that the willingness to adapt, community resilience, and government support play important roles in dealing with forest and peatland fires. Therefore, inter-stakeholder coordination should be conducted appropriately for effective risk management to benefit farmers and all impacted parties.